1997
DOI: 10.1073/pnas.94.16.8836
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cognition-specific cortical activity by gonadal steroids: A positron-emission tomography study in women

Abstract: There is considerable evidence from animal studies that gonadal steroid hormones modulate neuronal activity and affect behavior. To study this in humans directly, we used H 2 15 O positron-emission tomography to measure regional cerebral blood f low (rCBF) in young women during three pharmacologically controlled hormonal conditions spanning 4-5 months: ovarian suppression induced by the gonadotropin-releasing hormone agonist leuprolide acetate (Lupron), Lupron plus estradiol replacement, and Lupron plus proges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
185
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 304 publications
(194 citation statements)
references
References 32 publications
7
185
1
1
Order By: Relevance
“…Estradiol regulates PFC blood flow in humans (Berman et al 1997), and Korol (2002;2004) has demonstrated that E2 biases toward or against the activation of circuits mediating different forms of cognition: high estrogen favoring place-activated learning and low estrogen levels response-dependent learning. It is tempting to speculate, therefore, that disturbed ER alpha signaling in the luteal phase may interact with decreased PFC efficiency in those with the Val/ Val genotype so as to permit the expression of a dysphoric state suggestive of disinhibited subcortical (e.g., amygdala) activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estradiol regulates PFC blood flow in humans (Berman et al 1997), and Korol (2002;2004) has demonstrated that E2 biases toward or against the activation of circuits mediating different forms of cognition: high estrogen favoring place-activated learning and low estrogen levels response-dependent learning. It is tempting to speculate, therefore, that disturbed ER alpha signaling in the luteal phase may interact with decreased PFC efficiency in those with the Val/ Val genotype so as to permit the expression of a dysphoric state suggestive of disinhibited subcortical (e.g., amygdala) activity.…”
Section: Discussionmentioning
confidence: 99%
“…As such, we were interested in examining the significantly associated variants in ESR1 (multi-SNP association) against the background of gene polymorphisms that do not appear associated with the diagnosis of PMDD but may nevertheless be involved. The Val158Met polymorphism in the COMT gene was selected for the following reasons: 1) COMT is involved in estrogen metabolism, performing O-methylation of 2-and 4-hydroxy estrogen metabolites (catecholestrogens); 2) the COMT gene contains estrogen response elements (Xie et al 1999), consistent with its regulation (decrease) by estradiol in vitro (Jiang et al 2003), an effect that is presumed to be mediated by ER alpha (Jiang et al 2003); 3) COMT is implicated in sex steroid associated cancers (Tanaka et al 2006;Sazci et al 2004); 4) COMT is responsible for regulating dopamine levels in the PFC, which are critical for modulation of cognitive function and "tuning" of the PFC (the ratio of task-related to task-unrelated neuronal firing), and the PFC is a brain region in which estradiol has been shown to regulate cerebral blood flow and function in humans (Berman et al 1997;Keenan et al 2001); 5) the COMT Val/Met polymorphism has been linked to the predisposition to several psychiatric disorders, including schizophrenia and OCD (Tunbridge et al in press;Karayiorgou et al 1997) and has been shown to moderate the effects of environmental factors in determining disease expression (Caspi et al 2005). The manifold interactions of COMT and estradiol and their convergence in areas of the brain critical in regulating mood and hypothesized as dysfunctional in PMDD (Rubinow et al in press) provided compelling justification for investigation of possible epistasis (gene-gene interactions).…”
Section: Discussionmentioning
confidence: 99%
“…antioestrogens) have been examined with both neuroimaging (Berman et al, 1997) and neurocognitive probes (Varney et al, 1993, Rich andMaki, 1999). In summary, a pattern of relative hypometabolism in prefrontal cortex has been demonstrated with PET, and neurocognitive impairments in memory, executive function, and motor coordination have been reported.…”
Section: Hormonal Therapymentioning
confidence: 99%
“…The absence of such a hormone milieu results in a shift in development towards a phenotypic female brain [20]. In addition to generating sex differences in structural changes in the brain, estrogen is also responsible for the generation of sex differences in cognition and emotion [2,6,13,21].…”
Section: Introductionmentioning
confidence: 99%